Using Mining, Oil, and Gas Waste for Producing Environmental Warfare Ammunition - Fakron, Malik M.A. (Chemical Warfare and Environmental Warfare Operations, Edition 1, 2025)
Environmental warfare agents are Chemical weapons made of a chemical substance by using different natural processes such as hydrological cycles and rock cycles to release them on the battlefield. That reacts with the human body, causing death at a very small concentration in a very fast reaction rate. All industrial sectors, such as the oil and gas sector and mining industries, produce huge amounts of toxic chemical waste. These chemical wastes are promoted as raw materials for the development of environmental warfare agents. In fact, the main toxic elements for the human body are used in a wide range for different mines, gas fields and oil fields. Such as cyanide, carbon monoxide and hydrogen sulfide. This provides an opportunity for producing environmental warfare agents in solid state, liquid state and gas state from these waste materials. All agents are considered with their plan for introducing in natural cycles and the process time. This ammunition is distributed to these agents over the target area in a uniform way.